2019
DOI: 10.17628/ecb.2019.8.1-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Evaluation of New Benzenesulfonamide Derivatives

Abstract: A highly efficient protocol was developed for the synthesis of 3-(indoline-1-carbonyl)-N-(substituted)benzenesulfonamide compounds with excellent yields. The in vitro anticancer activity of the new 3-(indoline-1-carbonyl)-N-(substituted)benzenesulfonamide derivatives against A549 (lung cancer cell), HeLa (cervical), MCF-7 (breast cancer cell) and Du-145 (prostate cancer cell) cell lines were studied. Most of the tested compounds showed anticancer activity (IC50 values ranged between 1.98 and 9.12 µM against di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…With reference to above literature survey, in continuation to our previous research work of pharmaceutical moieties, 30–36 we have focused on synthesis of imidazo[1,2‐ a ]pyrimidine‐3‐carbonitrile derivatives (4a‐j ) using efficient and heterogeneous Zinc Ferrite (ZnFe 2 O 4 ) as nanocatalyzed one‐pot three‐component condensation reaction of benzimidazole ( 1 ) and malononitrile (3) with substituted aromatic aldehyde (2a‐j ) in methanol under ultrasonic irradiations. Author has selected normal spinel catalyst ZnFe 2 O 4 for present synthesis because ammonia molecule preferred to adsorbed on the surface of Zn atom of spinal zinc ferrite and it is used to removal of ammonia 37 .…”
Section: Introductionmentioning
confidence: 99%
“…With reference to above literature survey, in continuation to our previous research work of pharmaceutical moieties, 30–36 we have focused on synthesis of imidazo[1,2‐ a ]pyrimidine‐3‐carbonitrile derivatives (4a‐j ) using efficient and heterogeneous Zinc Ferrite (ZnFe 2 O 4 ) as nanocatalyzed one‐pot three‐component condensation reaction of benzimidazole ( 1 ) and malononitrile (3) with substituted aromatic aldehyde (2a‐j ) in methanol under ultrasonic irradiations. Author has selected normal spinel catalyst ZnFe 2 O 4 for present synthesis because ammonia molecule preferred to adsorbed on the surface of Zn atom of spinal zinc ferrite and it is used to removal of ammonia 37 .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] These reports suggested that Rhodanine nuclei were essential to the observed levels of antimicrobial activity. [25][26][27][28] We make a plan to synthesized Rhodanine derivatives as an antimicrobial agent by preparing hybrid molecules having similar features of reported potent antimicrobial agents (Figure 1). Because of the facts mentioned above, Rhodanine derivatives were synthesized, characterized by different spectral analysis techniques and screened for their antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…They showed a huge number of important biological properties such as antimicrobial, [4][5][6][7] antimalarial, [8][9][10] analgesic, 11 anthelmintic, 12 antitumor, 13 antiinflammatory, 14 antiviral [15][16][17] and anticancer 18 activity. Keeping the view of the biological importance of heterocyclic compounds, 19 we studied the biological activity of tetrahydroquinoline 20 pyrimidine, 21 thiazolone, 22 and benzenesulfonamide 23 derivatives.…”
Section: Introductionmentioning
confidence: 99%